A functional fluorinated polymer and its preparation method and application
Through the development of modified PVDF-based adhesives, aqueous vinyl phosphate monomers are used to improve their alkali resistance and dispersion, which solves the problems of insufficient adhesion and gelation in lithium-ion batteries, and improves the energy density of the batteries and electrode material properties.
Patent Information
- Application Number
- CN202410808123.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-06-21
AI Technical Summary
The existing fluorinated adhesive PVDF is insufficient in lithium-ion batteries, and is prone to gelation in highly alkaline environments, which affects the dispersion and processability of the electrodes, resulting in safety hazards and poor performance.
Functional fluoropolymer composed of 90.0 wt%~99.8 wt% VDF monomer and 0.2 wt%~10 wt% modified monomer was prepared by aqueous suspension polymerization method, and aqueous vinyl phosphate monomer was added to improve the The alkali resistance and dispersion of the adhesive form a high-performance PVDF-based adhesive.
It achieves low addition amount, high viscosity and high alkali resistance, improves the energy density of lithium-ion batteries, dispersibility and processability of electrode materials, and enhances the overall performance of the battery.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a PVDF-based functional fluorine-containing polymer. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in new energy storage industries such as information technology, consumer electronics, power tools, hybrid and all-electric vehicles, solar and wind power. However, lithium-ion batteries also face major problems such as increased internal resistance after long-term use, insufficient cycle performance and service life, and safety hazards during overheating or overcharging. Binders are one of the essential materials in the manufacturing process of lithium-ion batteries and are in great demand in the fields of battery pole pieces, diaphragms, packaging, etc. There are two main types of binders: fluorinated binders and non-fluorinated binders. PVDF-based polymers have become the current preferred cathode fluorinated binder material because they have higher oxidation resistance than other materials, which is an important requirement for long cycle life.
[0003] The existing fluorinated binder PVDF needs to be added in large quantities in the battery system with lithium iron phosphate as the active material to ensure that the pole piece has sufficient bonding force. At the same time, the binder cannot maintain sufficient flexibility during the cycle process, which makes the pole piece prone to brittle fracture, thereby causing safety problems. In addition, the nickel element in the ternary material is alkaline. The higher the Ni content, the stronger the alkalinity of the battery slurry prepared. The strong alkaline environment of the slurry will trigger the elimination reaction of the binder polyvinylidene fluoride (PVDF), resulting in gelation of the slurry, which directly affects the fluidity and processability of the slurry. The existing technical means to solve the above problems are usually solved by modifying PVDF and using acidic additives. At present, PVDF modification is mainly PVDF modified with strong polar groups, which can be used in conventional ternary systems, and the positive electrode slurry is not easy to gel. However, in the ternary positive electrode system with higher alkalinity, this copolymer-modified PVDF can still only ensure that it will not gel during stirring or in a short time. Therefore, the existing binders still need to be improved, and the development of high-performance PVDF-based binders is imperative.
[0004] Patent CN104804121A discloses a PVDF-based binary or multi-polymer modified with vinyl phosphate monomers for use in the field of water treatment membranes and coatings. The polymerization method is emulsion polymerization or suspension polymerization. Due to its application in the field of water membranes and coatings, the molecular weight of the synthesized polymer is low and insufficient to provide more hydroxyl groups, which is insufficient to achieve the requirements of low addition amount, high adhesion and high alkali resistance in the application field of lithium battery adhesives.
[0005] Patent CN101679563A discloses a vinylidene fluoride copolymer, which is prepared by copolymerizing hydrophilic (meth) acrylic monomers with vinylidene fluoride to prepare polyvinylidene fluoride resin. Its alkali resistance and adhesion are greatly improved compared with homopolymers, but its anti-gelling properties in high alkaline environmental conditions and its lack of dispersibility need to be further improved.
[0006] Patent CN109075344A discloses a vinylidene fluoride copolymer, which is a vinylidene fluoride copolymer with carboxyl acidic functional groups and has strong adhesiveness. However, the carboxyl group does not have self-dispersibility, and its hydrophilicity is also lower than that of the hydroxyl group. Although it has good adhesive properties, it may have gelation; and the monomers published therein have high molecular weight groups with heteroatoms and molecular weights less than 500, and the steric hindrance effect is not conducive to the copolymerization reaction of the monomers, and there may be a polymer "block structure". Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a functional fluorine-containing polymer with low addition amount, high bonding force and high alkali resistance and a preparation method thereof.
[0008] The technical solution adopted by the present invention to solve the technical problem is: a functional fluorine-containing polymer, the polymerization monomer of the polymer consists of 90.0wt% to 99.8wt% of VDF monomer and 0.2wt% to 10wt% of modified monomer;
[0009] The VDF monomer is a composite monomer of vinylidene fluoride monomer and fluorine-containing monomer;
[0010] The modified monomer includes at least one aqueous vinyl phosphate monomer as one of the repeating units.
[0011] The functional fluorine-containing polymer of the present invention solves the problem of insufficient adhesion of fluorinated adhesive PVDF in the battery system with lithium iron phosphate as the active material in the prior art. The present invention provides a high-performance PVDF-based polymer modified with vinyl phosphate, which further reduces the proportion of inactive components such as adhesives in the electrode and further improves the energy density of the battery; at the same time, the PVDF-based polymer acts as a "bridge" to provide better dispersibility, adhesion, and processability between active materials (such as lithium iron phosphate, lithium cobalt oxide, nickel cobalt manganese oxide, etc.), conductive carbon, metal foil and other electrode materials, giving lithium-ion batteries more excellent comprehensive performance.
[0012] Preferably, in the above-mentioned functional fluorine-containing polymer, the fluorine-containing monomer includes one or any combination of two or more of vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene or perfluoromethyl vinyl ether.
[0013] Preferably, in the above functional fluorine-containing polymer, the chemical formula of the water-based vinyl phosphate monomer is Chemical Formula I:
[0014] .
[0015] Wherein, R1, R2, and R3 are the same or different from each other, and can be a hydrogen atom or a C1-C3 hydrocarbon group. From the perspective of polymerization reaction theory, a substituent with small steric hindrance is preferred, preferably a hydrogen atom. R4 and R5 are hydrogen atoms.
[0016] Preferably, in the above functional fluorine-containing polymer, the aqueous vinyl phosphate monomer is vinyl phosphate.
[0017] Preferably, in the above functional fluorine-containing polymer, the modified monomer further comprises one or more structural monomers of Chemical Formula II as repeating units:
[0018] .
[0019] Wherein, R6, R7, R8 are the same or different from each other, and can be a hydrogen atom or a C1-C3 hydrocarbon group, preferably a hydrogen atom. R9 is a hydrogen atom or a hydrocarbon group containing a hydroxyl group; such as acrylic acid, hydroxyethyl acrylate, etc.
[0020] Preferably, in the functional fluorine-containing polymer, the mass ratio of the vinylidene fluoride monomer to the fluorine-containing monomer in the VDF monomer is 50-99:1-50. More preferably, the mass ratio of the vinylidene fluoride monomer to the fluorine-containing monomer in the VDF monomer is 90-99:1-10.
[0021] Preferably, the functional fluorine-containing polymer has a weight average molecular weight of 150 WDa to 220 WDa, and a molecular weight distribution of 1.5 to 2.5.
[0022] Preferably, the functional fluorine-containing polymer has an intrinsic viscosity of 2.5 dL / g to 5.0 dL / g and a melting point of 155° C. to 169° C. The polymer binder within this range can give the pole piece good flexibility and bonding strength.
[0023] Another object of the present invention is to create a novel method for synthesizing the functional vinylidene fluoride polymer. As the polymerization method of the vinylidene fluoride polymer, previously known suspension polymerization, emulsion polymerization, solution polymerization, etc. can be used, preferably aqueous suspension polymerization; the method advantageously includes preparing the functional polymer in a pure water medium in the presence of a dispersion medium.
[0024] A method for preparing the above functional fluorine-containing polymer comprises the following steps:
[0025] a) Adding composite dispersant and pure water to the polymerization reactor to displace and deoxygenate until the oxygen content is less than 20 ppm;
[0026] b) adding VDF monomer, chain transfer agent and initiator, and carrying out polymerization reaction under the reaction conditions of 25°C~60°C and 3.0MPa~12.0MPa, and adding the dispersion of modified monomer in water during the polymerization process;
[0027] c) After the reaction is completed, add composite dispersant, initiator and chain transfer agent.
[0028] Specifically, the composite dispersant in step c) is a ternary mixture of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol. Preferably, the weight ratio of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol is 1-10:1-10:1-10.
[0029] The preparation method of the present invention adds auxiliary agents such as an initiator and a molecular weight regulator in the presence of a dispersant, generates a PVDF-based modified polymer by free radical polymerization, and forms a powder by washing and drying the material, which can be used as an adhesive in lithium-ion batteries.
[0030] The dispersion of the modified monomer in water can be a single modified monomer or a mixed dispersion of multiple monomers, wherein the dispersion of the modified monomer in water can be initially added all at once, can be added in batches after initiation, or can be added continuously after initiation, preferably added continuously, which means adding the monomer aqueous solution slowly and in small amounts until the reaction is completed. During the entire operation, the reaction pressure applicable to the method of the present invention does not have to be maintained above the critical pressure of the vinylidene fluoride monomer. During low-temperature polymerization, the reaction pressure can be lower than the critical pressure of VDF. Special attention should be paid to the timing of adding the modified monomer. It must be ensured that there is enough VDF monomer in the polymerization kettle. The weight of VDF is a value that depends on temperature and pressure. The timing of adding the modified monomer can be determined based on the data displayed by the mass flowmeter;
[0031] In order to improve the dispersibility of the monomer in water, the bulkiness and regularity of the PVDF particles, and accelerate the dissolution rate of the adhesive in the NMP solvent, a composite dispersant is optionally added to the dispersion system. There is no particular restriction on the amount of the dispersant added, and it is mainly sufficient to improve the dispersibility of the monomer and not have an adverse effect on the subsequent polymerization reaction or the formed polymer.
[0032] Preferably, in the preparation method of the above-mentioned functional fluorine-containing polymer, the composite dispersant described in step c) includes two or more of a cellulose ether dispersant, a polysaccharide cyclodextrin series compound with a hollow cylindrical structure, and a polyvinyl alcohol dispersant, and the cellulose ether includes one or more of methyl cellulose, carboxyethyl cellulose, and hydroxypropyl cellulose; more preferably, the composite dispersant in step c) is a ternary composition of methyl cellulose, hydroxypropyl cellulose and polyvinyl alcohol.
[0033] Preferably, in the preparation method of the above-mentioned functional fluorine-containing polymer, the initiator is an organic peroxide, including one or more of tert-amyl peroxypivalate, tert-amyl peroxypivalate, diisopropyl peroxydicarbonate or di-n-propyl peroxydicarbonate; the chain transfer agent includes alcohols, ketones, esters, etc. Preferably, the chain transfer agent is one or a combination of ethyl acetate and isopropyl alcohol.
[0034] An application of a functional fluorine-containing polymer, wherein the functional fluorine-containing polymer is applied to an adhesive for positive electrode plates of lithium-ion batteries.
[0035] The sheet composition of the positive electrode sheet of a lithium-ion battery includes the following: the mass fraction of active material is 98-90%, the mass fraction of conductive agent is 1-5%, the mass fraction of adhesive is 0.8-2%, and the balance is other components. The calculation formula for the above total weight is the sum of the masses of active material, conductive agent, adhesive and other components.
[0036] The slurry of the lithium-ion battery only needs to be prepared into a uniform slurry containing a mixture of a solvent, a binder, a conductive agent, and an active material. The order of mixing is not particularly limited, and it is sufficient to ensure that the prepared positive electrode sheet has both excellent flexibility and good bonding strength.
[0037] The lamellar positive electrode active material of the positive electrode sheet of a lithium-ion battery includes at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present invention is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM111), LiNi 0.5 Co 0.2 Mn 0.3O2 (abbreviated as NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0 .15 Al 0 .05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate LiFePO4 (abbreviated as LFP), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0038] In a specific embodiment, the positive electrode conductive agent of the positive electrode layer of the lithium ion battery of the present invention includes one or more of conductive graphite, conductive carbon black, acetylene black, carbon nanotubes, and graphene;
[0039] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0040] The positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector. In specific use, the positive electrode current collector can be a metal foil or a composite current collector. For example, aluminum foil can be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer.
[0041] The electrode slurry may contain other components in addition to the above components. Examples of other components include dispersants such as polyvinyl pyrrolidone.
[0042] Compared with the prior art, the functional fluorine-containing polymer of the present invention and its preparation method and application have the following beneficial effects:
[0043] 1. Alkali resistance: PVDF-based copolymers modified with vinyl phosphate monomers have more -OH polar functional groups than PVDF-based polymers modified with acrylic acid, maleic acid and ester monomers, which endow PVDF with higher hydrophilicity and alkali resistance, especially in the ternary high-nickel active material system, which has strong alkali resistance and anti-gel performance.
[0044] 2. Low addition: The prepared hydrophilic PVDF-based copolymer has a P=O double bond structure that can form hydrogen bonds. Compared with PVDF homopolymer, it has higher adhesion with active materials and metal foils. A lower addition amount can give the electrode good adhesion properties.
[0045] 3. Self-dispersibility: The prepared hydrophilic PVDF-based copolymer is a polymer with a phosphate group structure and has self-dispersibility. It can enhance the interaction between the active material and the solvent, make the slurry particles easier to disperse, prevent the slurry from gelling, and give the electrode good dispersibility and processability.
[0046] 4. Rapid solubility: The prepared hydrophilic PVDF-based copolymer, in the presence of a composite dispersant, has a unique dispersion system that gives the PVDF particles a higher degree of fluffiness and regularity, making PVDF quickly soluble in NMP, and the glue is not easy to form "white clumps".
[0047] In summary, the functional fluorine-containing polymer and its preparation method of the present invention further reduce the proportion of inactive components such as adhesives in the electrode, and further improve the energy density of the battery; at the same time, the PVDF-based polymer acts as a "bridge" to provide better dispersibility, adhesion, and processability between active materials (such as lithium iron phosphate, lithium cobalt oxide, nickel cobalt manganese oxide, etc.), conductive carbon, metal foil and other electrode materials, giving lithium-ion batteries more excellent comprehensive performance. DETAILED DESCRIPTION
[0048] The present invention is described in detail below by way of examples. Unless otherwise specified, all raw materials used are commercially available.
[0049] The following examples were tested according to the following experimental scheme: Peel strength: Referring to GB-T2790, an electronic universal pull-off tester (CMT-5L) was used to measure the peel strength of the polymer after it was prepared into a positive electrode sheet at 180°;
[0050] Weight average molecular weight and molecular weight distribution coefficient: The weight average molecular weight and molecular weight distribution coefficient of the polymer were obtained by gel permeation chromatography (GPC 1260 Infinty II, Agilent), with polystyrene as the standard and dimethylacetamide as the mobile phase;
[0051] Melting point: The melting point of the polymer was determined by differential scanning calorimetry (DSC 3500, NETZSCH). The heating program was as follows: heating from 30°C to 200°C at a heating rate of 10°C / min, holding at 200°C for 10 minutes, cooling from 200°C to 50°C at a cooling rate of 10°C / min, holding at 50°C for 5 minutes, and heating from 50°C to 210°C at a heating rate of 10°C / min. The DSC spectrum at the second melting was recorded;
[0052] Intrinsic viscosity: refer to GB-T30514, dissolve the polymer in dimethylformamide, and measure it at 25℃ using Ubbelohde viscometer (NCY-2, Starda);
[0053] Example 1
[0054] A PVDF-based polymer prepared by moderate temperature polymerization of vinylidene fluoride monomers and vinyl phosphate monomers.
[0055] a) A vertical high-pressure polymerization kettle with a capacity of 100 L and equipped with a stirrer is charged with 50 kg of ultrapure water and 20 g of a ternary composite dispersant, wherein the weight ratio of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol in the ternary composite dispersant is 5:5:5, and then nitrogen is repeatedly injected and vacuumed to remove oxygen, so that the oxygen content in the polymerization kettle is less than 20 ppm.
[0056] b) Add VDF monomer with a mass ratio of vinylidene fluoride monomer to fluorine-containing monomer of 95:5 to make the pressure of the polymerization kettle slightly positive, raise the temperature to the polymerization temperature of 50°C, open the VDF feeding valve to feed VDF to increase the pressure, and when the pressure in the kettle reaches the critical pressure of VDF, add 10g of vinyl phosphoric acid, continue to add VDF until the pressure of the reactor reaches 8.0MPa, add 80g of tert-amyl peroxypivalate mineral oil solution, and start the reaction timing.
[0057] c) During the entire polymerization reaction, an aqueous solution including 45g of vinyl phosphoric acid was continuously added to keep the pressure of the polymerization kettle constant at more than 1.5 times the critical pressure value of VDF. After the monomer aqueous solution was added, the reaction was continued until the pressure of the reactor reached the critical pressure value of VDF, and the pressure was recovered and released to stop the polymerization reaction. The obtained polymer slurry was washed, dehydrated, and dried to obtain a functional group-modified vinylidene fluoride copolymer (VDF-co-VPA copolymer).
[0058] Example 2
[0059] A PVDF-based polymer prepared by moderate temperature polymerization of vinylidene fluoride monomers and vinyl phosphate monomers.
[0060] a) 60 kg of ultrapure water and 40 g of a ternary composite dispersant were added to a 100 L vertical high-pressure polymerization kettle equipped with a stirrer, wherein the weight ratio of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol in the ternary composite dispersant was 5:5:5, and then nitrogen was repeatedly injected and vacuum was used to remove oxygen, so that the oxygen content in the polymerization kettle was less than 20 ppm.
[0061] b) Add VDF monomer in a mass ratio of 90:10 between vinylidene fluoride monomer and fluorine-containing monomer to make the polymerization kettle pressure slightly positive, raise the temperature to the polymerization temperature of 55°C, open the VDF feeding valve to feed VDF to increase the pressure, and when the pressure in the kettle reaches the critical pressure of VDF, add 10g of vinyl phosphoric acid, continue to add VDF until the pressure of the reactor reaches 8.0MPa, add 80g of tert-amyl peroxypivalate solution in mineral oil, and start the reaction timing.
[0062] c) During the entire polymerization reaction, 15g of vinyl phosphoric acid aqueous solution was added for every 5kg of VDF added, and the polymerization kettle pressure was kept constant at 8.0MPa. When the amount of VDF added reached 15kg, the addition of VDF was stopped, and the reaction was continued until the pressure of the reactor reached the critical pressure of VDF, and the pressure was recovered and released to stop the polymerization reaction. The obtained polymer slurry was washed, dehydrated, and dried to obtain a functional group-modified vinylidene fluoride copolymer (VDF-co-VPA copolymer).
[0063] Example 3
[0064] A PVDF-based polymer prepared by low temperature polymerization of vinylidene fluoride monomers and vinyl phosphate monomers.
[0065] a) 50 kg of ultrapure water and 60 g of a ternary composite dispersant were added to a 100 L high-pressure polymerization kettle equipped with a stirrer, wherein the weight ratio of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol in the ternary composite dispersant was 5:5:5, and then nitrogen was repeatedly injected and vacuum was used to remove oxygen, so that the oxygen content in the polymerization kettle was less than 20 ppm.
[0066] b) Add VDF monomer in a mass ratio of 99:1 between vinylidene fluoride monomer and fluorine-containing monomer to make the pressure of the polymerization kettle slightly positive, raise the temperature to the polymerization temperature of 25°C, open the VDF feeding valve to feed 15 kg of VDF, add 10 g of vinyl phosphoric acid, and add 60 g of diisopropyl peroxydicarbonate initiator (50 wt%).
[0067] c) During the entire polymerization reaction, the pressure of the polymerization reactor was kept constant by continuously adding a mixed aqueous solution including 45g of vinyl phosphoric acid and 15g of chain transfer agent isopropanol. After the monomer aqueous solution was added, the pressure dropped to 2.5MPa, and the pressure was recovered and released to stop the polymerization reaction. The obtained polymer slurry was washed, dehydrated and dried to obtain a functional group-modified vinylidene fluoride copolymer (VDF-co-VPA copolymer).
[0068] Example 4
[0069] A PVDF-based polymer prepared by moderate temperature polymerization of vinylidene fluoride monomers and vinyl phosphate monomers.
[0070] a) 50 kg of ultrapure water and 40 g of a ternary composite dispersant were added to a 100 L high-pressure polymerization kettle equipped with a stirrer, wherein the weight ratio of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol in the ternary composite dispersant was 1:10:1, and then nitrogen was repeatedly injected and vacuum was used to remove oxygen, so that the oxygen content in the polymerization kettle was less than 20 ppm.
[0071] b) Add VDF monomer in a mass ratio of 50:50 between vinylidene fluoride monomer and fluorine-containing monomer to make the polymerization kettle pressure slightly positive, raise the temperature to the polymerization temperature of 50°C, open the VDF feeding valve to feed VDF to increase the pressure, and when the pressure in the kettle reaches the critical pressure of VDF, add 50g of vinyl phosphoric acid, continue to add VDF until the pressure of the reactor reaches 10.0MPa, add 120g of tert-amyl peroxypivalate solution in mineral oil, and start the reaction timing.
[0072] c) During the entire polymerization reaction, the pressure of the polymerization kettle was kept constant at more than 1.5 times the critical pressure of VDF by continuously adding an aqueous solution including 360g of vinyl phosphoric acid. After the monomer aqueous solution was added, the reaction was continued until the pressure of the reactor reached the critical pressure of VDF, and the pressure was recovered and released to stop the polymerization reaction. The obtained polymer slurry was washed, dehydrated, and dried to obtain a functional group-modified vinylidene fluoride copolymer (VDF-co-VPA copolymer).
[0073] Example 5
[0074] A PVDF-based polymer prepared by medium-temperature polymerization of vinylidene fluoride monomer, vinyl phosphate monomer and acrylic acid monomer.
[0075] a) 50 kg of ultrapure water and 50 g of a ternary composite dispersant were added to a 100 L high-pressure polymerization kettle equipped with a stirrer, wherein the weight ratio of methylcellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol in the ternary composite dispersant was 10:1:10, and then nitrogen was repeatedly injected and vacuum was used to remove oxygen, so that the oxygen content in the polymerization kettle was less than 20 ppm.
[0076] b) Add VDF monomer in a mass ratio of 75:25 between vinylidene fluoride monomer and fluorine-containing monomer to make the polymerization kettle pressure slightly positive, raise the temperature to the polymerization temperature of 52°C, open the VDF feeding valve to feed VDF to increase the pressure, and when the pressure in the kettle reaches the critical pressure of VDF, add 10g of vinyl phosphoric acid, continue to add VDF until the pressure of the reactor reaches 8.0MPa, add 90g of tert-amyl peroxypivalate solution in mineral oil, and start the reaction timing.
[0077] c) During the entire polymerization reaction, the pressure of the polymerization kettle was kept constant at more than 1.5 times the critical pressure of VDF by continuously adding a mixed aqueous solution including 30g of vinyl phosphoric acid and 15g of acrylic acid. After the monomer aqueous solution was added, the reaction was continued until the pressure of the reactor reached the critical pressure of VDF, and the pressure was recovered and released to stop the polymerization reaction. The obtained polymer slurry was washed, dehydrated and dried to obtain a functional group-modified vinylidene fluoride copolymer (VDF-co-VPA-co-AA copolymer).
[0078] Comparative Example 1
[0079] A PVDF homopolymer prepared by suspension homopolymerization of vinylidene fluoride monomer.
[0080] a) A vertical high-pressure polymerization kettle with a capacity of 100 L and equipped with a stirrer was charged with 55 kg of ultrapure water and 30 g of methyl cellulose as a suspending dispersant, and then the oxygen content in the polymerization kettle was reduced to less than 20 ppm by repeated nitrogen injection and vacuum extraction to remove oxygen.
[0081] b) Add VDF monomer with a mass ratio of vinylidene fluoride monomer to fluorine-containing monomer of 95:5 to make the polymerization kettle pressure slightly positive, raise the temperature to the polymerization temperature of 45°C, open the VDF feeding valve to feed VDF to increase the pressure of the reactor to 8.0 MPa, add 100g of tert-amyl peroxypivalate solution in mineral oil, add 10g of a mixture of ethyl acetate and isopropanol as a chain transfer agent, and start the reaction timing.
[0082] c) During the entire polymerization reaction, no additives are added, and the pressure in the reactor is maintained by adding VDF monomer. After a certain amount of VDF monomer reacts, the addition of VDF is stopped, and the reaction is continued until the pressure in the reactor reaches the critical pressure value of VDF, and the pressure is recovered and released to stop the polymerization reaction. The obtained polymer slurry is washed, dehydrated, and dried to obtain a functional group-modified vinylidene fluoride homopolymer (PVDF).
[0083] Comparative Example 2
[0084] A PVDF-based polymer, prepared by medium-temperature polymerization of vinylidene fluoride monomer and vinyl phosphate monomer (trace monomer + one-time addition).
[0085] a) A vertical high-pressure polymerization kettle with a capacity of 100 L equipped with a stirrer was charged with 55 kg of ultrapure water and 30 g of hydroxypropyl methylcellulose as a suspending dispersant, and then nitrogen was repeatedly injected and vacuumed to remove oxygen, so that the oxygen content in the polymerization kettle was less than 20 ppm.
[0086] b) Add VDF monomer with a mass ratio of vinylidene fluoride monomer to fluorine-containing monomer of 95:5 to make the pressure of the polymerization kettle slightly positive, raise the temperature to the polymerization temperature of 50°C, open the VDF feeding valve to feed VDF to increase the pressure, and when the pressure in the kettle reaches the critical pressure of VDF, add 55g of vinyl phosphoric acid at one time, continue to add VDF until the pressure of the reactor reaches 8.0MPa, add 80g of tert-amyl peroxypivalate solution in mineral oil, and start the reaction timing.
[0087] c) In the late stage of the entire polymerization reaction, 10 g of chain transfer agent ethyl acetate was added, and the pressure in the autoclave was maintained by adding VDF monomer. After a certain amount of VDF monomer reacted, the addition of VDF was stopped, and the reaction was continued until the pressure in the reactor reached the critical pressure value of VDF. The pressure was recovered and released, and the polymerization reaction was stopped to obtain a vinylidene fluoride copolymer modified with functional groups (VDF-co-VPA copolymer).
[0088] Comparative Example 3
[0089] Commercially available PVDF-based polymer: Solef 5130.
[0090] The physical property test results of the embodiments and comparative examples are shown in Table 1.
[0091] Table 1 Physical property test results of various examples and comparative examples
[0092] .
[0093] Application Example 1
[0094] Preparation of positive electrode:
[0095] NCA811 was used as the electrode active material, and carbon black as a conductive aid and the PVDF-based polymer prepared in Preparation Example 4 were added to NCA811 for powder mixing. N-methylpyrrolidone solvent was added to prepare a positive electrode slurry (electrode active material: carbon black: PVDF copolymer 96:2:2); two portions of the slurry were prepared, one for tracking the slurry stability and the other for coating to test the electrode peel strength.
[0096] Application Example 2
[0097] Preparation of positive electrode sheet: Based on Example 1, the binder is changed to the PVDF binder in Comparative Example 3.
[0098] Application Example 3
[0099] Preparation of positive electrode sheet: lithium iron phosphate was used as the electrode active material, carbon black as a conductive aid and the PVDF-based polymer prepared in Example 1 were added to the lithium iron phosphate for powder mixing. N-methylpyrrolidone solvent was added to prepare positive electrode slurry (electrode active material: carbon black: PVDF 97:2:1); two portions of slurry were prepared, one for tracking slurry stability and the other for coating to test the peel strength of the electrode sheet.
[0100] Application Example 4
[0101] Preparation of positive electrode sheet: Based on Application Example 1, the adhesive is changed to the PVDF adhesive of Example 5.
[0102] Application Example 5
[0103] Preparation of positive electrode sheet: Based on Application Example 1, the adhesive is changed to the PVDF adhesive of Comparative Example 2.
[0104] Application Example 6
[0105] Preparation of positive electrode sheet: Based on Application Example 1, the adhesive is changed to the PVDF adhesive of Comparative Example 1.
[0106] The performance test results of the application example are shown in Table 2.
[0107] Table 2 Performance test results of various application examples
[0108] .
[0109] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A functional fluorinated polymer, It is characterized in that The polymerization monomers of the polymer are composed of 90.0wt% to 99.8wt% of VDF monomer and 0.2wt% to 10wt% of modified monomer; The VDF monomer is a composite monomer of vinylidene fluoride monomer and fluorine-containing monomer in a mass ratio of 90-99:1-10; The modified monomer includes vinyl phosphoric acid as one of the repeating units; The preparation method comprises the following steps: a) Add composite dispersant and pure water to the polymerization reactor to displace and deoxygenate until the oxygen content is less than 20 ppm; b) adding VDF monomer, chain transfer agent and initiator, and carrying out polymerization reaction under the reaction conditions of 25°C~60°C and 3.0MPa~12.0MPa, and adding the dispersion of modified monomer in water during the polymerization process; c) adding composite dispersant, initiator and chain transfer agent after the reaction is completed; The composite dispersant in step c) is a ternary mixture of methyl cellulose, hydroxypropyl-β-cyclodextrin and polyvinyl alcohol in a mass ratio of 1-10:1-10:1-10.
2. A functional fluorine-containing polymer according to claim 1, It is characterized in that The fluorine-containing monomer includes one or any combination of two or more of vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene or perfluoromethyl vinyl ether.
3. A functional fluorine-containing polymer according to claim 1, It is characterized in that The weight average molecular weight of the polymer is 150WDa-220WDa, and the molecular weight distribution is 1.5-2.
5.
4. A functional fluorine-containing polymer according to claim 1, It is characterized in that The polymer has an intrinsic viscosity of 2.5 dL / g to 5.0 dL / g and a melting point of 155° C. to 169° C.
5. Application of a functional fluorinated polymer, It is characterized in that The functional fluorinated polymer according to any one of claims 1 to 4 is used as an adhesive for positive electrode sheets of lithium-ion batteries.
Citation Information
Patent Citations
Vinylidene fluoride copolymers
CN101679563A
Novel hydrophilic modified vinylidene fluoride copolymer
CN104804121A
Binder composition, electrode mixture, electrode, non-aqueous electrolyte secondary battery, and binder composition production method
CN109075344A
Functional fluoropolymers
CN111954658A
